Best practices for graphics in metropolitan transportation plans - Foss, Rachel Briana (Kansas State University, 2019)
There are over four-hundred metropolitan planning organizations (MPOs) in the United States that are federally required to communicate regional long-range priorities in their Metropolitan Transportation Plan (MTP). These plans provide a long-term vision that drives the prioritization and development of billions of dollars worth of transportation improvement projects. Despite the value of these plans, most MTPs fall short on their ability to feel user-friendly (Florida Department of Transportation, 2013). One explanation may be the fact that there is a lack of guidance for good graphic communication. MPOs need to think strategically about how to visualize their information. Therefore, this research is intended to serve as a resource to create appealing and more effective graphics for the general public, stakeholders, and elected officials. Over 1,500 graphics were carefully researched from a random selection of twenty MTPs from MPOs across the United States (with a population less than 200,000). Each graphic was categorized into one of three graphic types used within MTP documents: spatial, numeric, and concept graphics. Extensive quantitative analysis was conducted on these graphics in order to understand existing practice among the twenty MTPs. The application of graphic communication principles for these graphic types enable MPO planners and decision makers to understand "best practices" for graphics in MTP documents. In turn, these recommendations have the ability to enhance the way information is presented publicly and strengthen the overall quality of a document that serves as the overarching regional transportation vision for the future.
Keywords: Graphics; Transportation Planning; Long-Range Plan